The Age of Genius : the seventeenth century and the birth of the modern mind - Grayling, A. C. (Bloomsbury, 2016)
"Explores the eventful intertwining of outward event and inner intellectual life to tell, in all its richness and depth, the story of the 17th century in Europe. It was a time of creativity unparalleled in history before or since, from science to the arts, from philosophy to politics ... Grayling points to three primary factors [behind this epochal shift]: the rise of vernacular (popular) languages in philosophy, theology, science, and literature; the rise of the individual as a general and not merely an aristocratic type; and the invention and application of instruments and measurement in the study of the natural world"--Amazon.com.